A room temperature magnetostrictive composite material and preparation method thereof
By regulating the internal stress of CoMnSi particles and preparing CoMnSi/epoxy resin composite materials, the existing magnetostrictive materials have been solved, and the low-cost and efficient room temperature magnetostrictive effect is achieved.
Patent Information
- Application Number
- CN202310275125.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-03-21
AI Technical Summary
Existing magnetostrictive materials such as Terfenol-D alloys limit their practical applications due to their expensive raw materials, scarce and complex preparation processes; while CoMnSi-based alloys are cheap, they are brittle and have a large critical field of magnetic phase transition, making it difficult to achieve efficient magnetostriction at room temperature.
The internal stress of CoMnSi particles is regulated through the quenching-tempering process, the critical field of magnetic phase transition is reduced, and a high volume fraction of CoMnSi/epoxy resin composite material is prepared by magnetic field curing method to achieve dense orientation of the material and high magnetostrictive effect under low driving magnetic field.
The low-cost and simple preparation process of CoMnSi materials is realized, and the huge magnetostrictive effect of 600 ppm is achieved at room temperature, which promotes the process of materials in magnetostrictive applications.
Smart Images

Figure CN116178897B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials, and in particular relates to a room temperature magnetostrictive composite material and a preparation method thereof. Background Art
[0002] Magnetostrictive materials refer to magnetic materials that stretch or shorten in the direction of magnetization when magnetized in a magnetic field. Magnetostrictive materials have many excellent physical properties such as high energy density, high conversion efficiency, fast response speed, and simple driving method. Therefore, they are widely used in shock absorption and shockproof, marine and offshore engineering, automation technology, micro-displacement drive and other fields. Among them, oriented Terfenol-D alloy (Tb x Dy (1-x) Fe2, 0.27≤x≤0.35) can obtain a giant magnetostrictive effect of 1600 ppm under a 1 T magnetic field. Terfenol-D alloy has the characteristics of small driving magnetic field, large stress output, and large strain output. It is currently the most famous and widely used magnetostrictive material. However, the raw materials of Terfenol-D alloy contain expensive heavy rare earth elements: Tb and Dy. The expensive cost, scarcity of raw materials, intrinsic brittleness and strict preparation process limit the practical application of the material. At present, there is still an urgent need for a cheap and recyclable magnetostrictive material on the market.
[0003] In recent years, CoMnSi-based alloys have attracted attention as a potential magnetostrictive material. Below its Neel temperature, the material undergoes a transition from a helical antiferromagnetic state to a ferromagnetic state (AFM-FM) induced by a magnetic field. This magnetic phase transition is accompanied by a dramatic anisotropic lattice distortion, making CoMnSi a potential magnetostrictive material. In 2010, Barcza et al. observed that Co at 280K 0.95 Ni 0.05 During the magnetic phase transition of small particles of MnSi alloy oriented along the a-axis, the magnetostrictive effect reaches about -1200 ppm, which is comparable to some rare earth alloys. Compared with rare earth giant magnetostrictive materials, CoMnSi-based alloys have the following advantages as magnetostrictive materials: (1) The raw materials are cheap and easy to obtain. The main raw materials of CoMnSi-based alloys are transition metals and main group elements. Compared with expensive and rare rare earth elements, CoMnSi is cheaper and the raw materials are easier to obtain. (2) CoMnSi does not contain rare earths and the preparation process is relatively simple. The above factors have greatly improved the practical value of CoMnSi.
[0004] However, CoMnSi-based alloys still face many difficulties as magnetostrictive materials: (1) CoMnSi bulk materials are brittle and have poor plasticity; (2) The critical field of the magnetic phase transition of CoMnSi is very large, about 2.5 T at room temperature, which makes it difficult to use in practice; (3) The magnetostrictive performance of CoMnSi polycrystalline bulk materials is small, and the linear magnetostrictive effect is only about 700 ppm. The preparation of oriented and dense CoMnSi bulk materials is the mainstream direction of current research. In 2015, Gong Yuanyuan et al. proposed a process of directional solidification and slow cooling in a strong magnetic field, and successfully prepared dense <111> The oriented CoMnSi bulk material significantly reduced the critical field of the magnetic phase transition of CoMnSi by the absence of Si elements, and achieved a giant magnetostrictive effect of -4100 ppm near room temperature. In 2018, Hu Qiubo and others also used the strong magnetic field directional solidification and slow cooling process to prepare CoMn 0.88 Si and CoMn 0.97 Fe 0.03 Si textured bulk. They used the vacancies of Mn elements and the doping of Fe elements to significantly reduce the critical field of the alloy's magnetic phase transition and the saturation field of the magnetostrictive effect. At 290 K, CoMn 0.88 The critical field of magnetic phase transition of Si alloy is reduced to around 1 T, while the saturation magnetic field of magnetostrictive effect is reduced to around 2 T, and a magnetostrictive effect of -2500 ppm is achieved around 3 T. However, the high magnetic field directional solidification technology requires a strong magnetic field of more than 6 T, and the preparation process is harsh and difficult to apply in practice.
[0005] CoMnSi-based alloy / epoxy resin composites are another way to prepare oriented and dense CoMnSi bulk materials. Finding CoMnSi-based alloy particles with high magnetostriction at low driving magnetic field at room temperature is the key to preparing CoMnSi-based composites. The critical field of the room temperature magnetic phase transition of CoMnSi alloy is about 2.5 T. Researchers often use element doping and vacancy to reduce the critical field: Zhang Chengliang et al. replaced Co with Ni and Si with Ge; Gong Yuanyuan et al. introduced Si element vacancy in CoMnSi and used B to replace Si; Morrison et al. replaced Mn with Fe and Mn with Ni; Hu Qiubo et al. introduced Mn element vacancy and other methods. In CoMnSi alloy, Mn element is the main bearer of the material's magnetism, and the nearest neighbor spacing of Mn element, the order of atomic arrangement, etc. directly determine the magnetic structure of CoMnSi. Therefore, internal stress is likely to affect the magnetism of CoMnSi, and we are expected to regulate the internal stress of CoMnSi material by changing the heat treatment process, thereby regulating the magnetic phase transition of CoMnSi and the continuous change of the critical field of magnetic phase transition. At present, there are almost no reports or inventions on regulating the magnetic properties of CoMnSi by heat treatment. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a room temperature magnetostrictive composite material and a preparation method thereof. The method utilizes the quenching-tempering process to regulate the internal stress of the positively divided CoMnSi particles, thereby making the CoMnSi magnetic phase transition critical field continuously change. On this basis, a high volume fraction oriented and dense CoMnSi / epoxy resin composite material is prepared by magnetic field curing. The preparation method has the characteristics of simple synthesis route, low production cost and continuous controllable driving magnetic field.
[0007] In order to achieve the above object, the present invention provides the following scheme:
[0008] A room temperature magnetostrictive composite material, characterized in that it is a dense CoMnSi alloy particle / epoxy resin composite material, the molecular formula of the alloy particle is CoMnSi, and the epoxy resin contains a polymer containing more than two epoxy groups in the molecule.
[0009] Furthermore, the CoMnSi alloy particles in the composite material exhibit <013> , <020> Preferred orientation, the volume fraction of alloy particles is higher than 50%.
[0010] The present invention also provides a method for preparing the above-mentioned magnetostrictive material, comprising the following steps:
[0011] a. The CoMnSi alloy ingot is crushed into particles of 30-300 μm by mechanical crushing, mortar grinding, etc. for later use;
[0012] b. Evacuate the quartz tube obtained in step a, fill it with argon gas to 0.02 MPa and seal it;
[0013] c. Place the quartz tube obtained in step b into a high temperature furnace, heat it from room temperature to 1000-1100°C and keep it for 6-24 h, then cool it to 900-1000°C at a rate of 10°C / min and keep it for 0.5-12 h, finally take out the quartz tube and quickly break it in cooling water;
[0014] d. Collect the CoMnSi particles obtained in step c by magnetic attraction, and dry the CoMnSi particles;
[0015] e. Place the CoMnSi particles obtained in step d into a quartz tube and seal it under vacuum;
[0016] f. Place the quartz tube obtained in step e into a high temperature furnace, heat to 600-850° C., keep warm for 0.5- 2 h, and cool naturally to room temperature to obtain CoMnSi particles;
[0017] g. Mix the CoMnSi particles obtained in step f with epoxy resin in an appropriate volume ratio, place them in a mold, and cure them in a uniform magnetic field with an intensity of 0.1-2T for 6-24 hours.
[0018] Furthermore, in step a, the CoMnSi alloy ingot can be obtained by an ingot preparation method such as arc melting method, induction melting method, etc.;
[0019] Furthermore, in step b, a mechanical pump is used to draw the vacuum to below 10 Pa, and then a molecular pump is used to draw the vacuum to 1×10 -3 Pa, turn off the molecular pump and fill with argon to 0.6 atmospheres;
[0020] Furthermore, in step d, the CoMnSi particles may be dried using an oven, a hair dryer, or the like;
[0021] Furthermore, in step e, a mechanical pump is used to draw the vacuum to below 10 Pa, and then a molecular pump is used to draw the vacuum to 1×10 -3 Pa seal;
[0022] Furthermore, in step g, the volume ratio of CoMnSi to epoxy resin needs to be higher than 1:1;
[0023] Furthermore, in step g, the magnetic field strength is determined by the magnetism of CoMnSi, and the strength is generally between 0.1-2T.
[0024] The present invention discloses the following technical effects:
[0025] 1. A room temperature magnetostrictive composite material and a preparation method thereof of the present invention are composed of positively divided CoMnSi alloy particles and epoxy resin. Compared with rare earth giant magnetostrictive materials, the material has low cost and simple preparation process.
[0026] 2. The CoMnSi particles prepared by the preparation process of the present invention regulate the internal stress in the CoMnSi particles by changing the heat treatment process, so that the critical magnetic field of the magnetic phase transition of CoMnSi is continuously controllable, and the critical field of the magnetic phase transition of CoMnSi can be significantly reduced.
[0027] 3. A room temperature magnetostrictive composite material of the present invention, wherein the CoMnSi particles exhibit <013> , <020> Due to the phenomenon of preferred orientation, the composite material achieved a giant magnetostrictive effect of 600 ppm in both parallel and perpendicular directions near 1T, which promoted the application of CoMnSi materials in magnetostriction. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the magnetization curve of CoMnSi particles in detection example 1.
[0029] Figure 2 This is the XRD characterization of the CoMnSi composite material in Example 1 before orientation.
[0030] Figure 3 The magnetostrictive properties of the CoMnSi composite material in Example 1 are tested.
[0031] Figure 4 This is the magnetization curve of the CoMnSi particles in Example 2.
[0032] Figure 5 It is the magnetization curve of the CoMnSi epoxy resin composite material in Example 3. Implementation
[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0034] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. Example 1
[0036] a. Obtain CoMnSi intermetallic compound (subscript is atomic percentage) by smelting method, and mechanically crush to obtain powder with average size of about 50μm to 100μm;
[0037] b. Take 10 g of CoMnSi metal powder and put it into a quartz tube. Evacuate the quartz tube to 1.0×10 -3 Sealing the tube after Pa;
[0038] c. Place the quartz tube in a high-temperature furnace heated to 1000°C for 1 hour, cool it down to 950°C at a cooling rate of 10°C / min, take out the quartz tube and quickly break the tube wall in cooling water for quenching;
[0039] d. Collect the CoMnSi alloy particles with a magnet and dry the alloy particles in an oven;
[0040] e. Place the collected CoMnSi particles into a quartz tube and evacuate the tube to a vacuum of 1.0×10 -3 Pa seal;
[0041] f. Place the quartz tube in an annealing furnace heated to 800°C for 0.5 h, and then cool it to room temperature;
[0042] g. Mix the CoMnSi particles obtained in step f with epoxy resin in a volume ratio of 3:2, place them in a mold, and cure them in a uniform magnetic field with a strength of 0.2 T for 24 h.
[0043] Figure 1 The magnetization curves of the CoMnSi particles obtained in step c and step f are shown in FIG. The rapidly quenched CoMnSi particles obtained in step c exhibit ferromagnetism, and the tempered CoMnSi obtained in step f exhibits obvious magnetic phase transition characteristics, with a critical field of about 0.5 T, which is much lower than 2.5 T at room temperature. Figure 2 The XRD diagram of the CoMnSi particles before orientation in step c and step f and the CoMnSi composite material after orientation in step g. After orientation, the CoMnSi composite material showed obvious preferential orientation phenomenon, and the (013) (020) peak height was significantly enhanced. Figure 3 The magnetostrictive properties of the CoMnSi composite material in the parallel and perpendicular directions after orientation in step g are characterized. At 1 T magnetic field, the CoMnSi composite material exhibits a magnetostrictive effect of nearly 600 ppm in the parallel and perpendicular directions. Example 2
[0044] a. Obtain CoMnSi intermetallic compound (subscript is atomic percentage) by smelting method, and mechanically crush to obtain powder with average size of about 50μm to 100μm;
[0045] b. Take 10 g of CoMnSi metal powder and put it into a quartz tube. Evacuate the quartz tube to 1.0×10 -3 Sealing the tube after Pa;
[0046] c. Place the quartz tube in a high-temperature furnace heated to 1000°C for 1 hour, cool it down to 950°C at a cooling rate of 10°C / min, take out the quartz tube and quickly break the tube wall in cooling water for quenching;
[0047] d. Collect the CoMnSi alloy particles with a magnet and dry the alloy particles in an oven;
[0048] e. Place the collected CoMnSi particles into a quartz tube and evacuate the tube to a vacuum of 1.0×10 -3 Pa seal;
[0049] f. Place the quartz tube in an annealing furnace heated to 800°C for 1 h, 2 h, 6 h, and 12 h, and then cool to room temperature along with the furnace;
[0050] g. Mix the CoMnSi particles obtained in step f with epoxy resin in a volume ratio of 3:2, place them in a mold, and cure them in a uniform magnetic field with a strength of 0.2 T for 24 h.
[0051] Figure 4 The magnetization curves of the CoMnSi particles obtained in step c and step f are shown in FIG. The rapidly quenched CoMnSi particles obtained in step c exhibit ferromagnetism, and the tempered particles obtained in step f have a gradually changing magnetism and a gradually increasing critical field as the tempering time increases. Example 3
[0052] a. Obtain CoMnSi intermetallic compound (subscript is atomic percentage) by smelting method, and mechanically crush to obtain powder with average size of about 50μm to 100μm;
[0053] b. Take 10 g of CoMnSi metal powder and put it into a quartz tube. Evacuate the quartz tube to 1.0×10 -3 Sealing the tube after Pa;
[0054] c. Place the quartz tube in a high-temperature furnace heated to 1000°C for 1 hour, cool it down to 950°C at a cooling rate of 10°C / min, take out the quartz tube and quickly break the tube wall in cooling water for quenching;
[0055] d. Collect the CoMnSi alloy particles with a magnet and dry the alloy particles in an oven;
[0056] e. Place the collected CoMnSi particles into a quartz tube and evacuate the tube to a vacuum of 1.0×10 -3 Pa seal;
[0057] f. Place the quartz tube in an annealing furnace heated to 800°C for 0.5 h, and then cool it to room temperature;
[0058] g. Mix the CoMnSi particles obtained in step f with epoxy resin in a volume ratio of 3:2, place them in a mold, and cure them in a uniform magnetic field with intensities of 0.1, 0.3, and 0.5 T for 24 h.
[0059] Figure 5 The magnetization curve of the CoMnSi epoxy resin composite material obtained in step g. When oriented in a magnetic field, the CoMnSi composite material exhibits different degrees of preferential orientation, and the (013) (020) peak heights are enhanced.
[0060] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. The present invention will not be limited to the embodiments shown herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a room temperature magnetostrictive composite material, characterized in that: The following steps are involved: a. Crushing the CoMnSi alloy ingot into particles of 30-300 μm by mechanical crushing or mortar grinding for later use; b. Place the CoMnSi alloy particles prepared in step a into a quartz tube, evacuate the tube, and fill the tube with argon gas to 0.02 MPa to seal the tube; c. Place the quartz tube obtained in step b into a high temperature furnace, heat it from room temperature to 1000-1100°C and keep it for 6-24 h, then cool it to 900-1000°C at a rate of 10°C / min and keep it for 0.5-12 h, finally take out the quartz tube and quickly break it in cooling water; d. Collect the CoMnSi particles obtained in step c by magnetic attraction, and dry the CoMnSi particles; e. Place the CoMnSi particles obtained in step d into a quartz tube and seal it under vacuum; f. placing the quartz tube obtained in step e into a high temperature furnace, heating it to 600-850° C., keeping it warm for 0.5-2 hours, and naturally cooling it to room temperature to obtain CoMnSi particles; g. Mix the CoMnSi particles obtained in step f with epoxy resin in an appropriate volume ratio, place in a mold, and cure in a uniform magnetic field with an intensity of 0.1-2T for 6-24 h to obtain CoMnSi composite particles, wherein the epoxy resin is a polymer containing two or more epoxy groups in the molecule, and the CoMnSi composite particles exhibit <013> , <020> Select the best orientation.
2. The method for preparing a room temperature magnetostrictive composite material according to claim 1, characterized in that: In step a, the CoMnSi alloy ingot is obtained by an arc melting method or an induction melting method.
3. The method for preparing a room temperature magnetostrictive composite material according to claim 1, characterized in that: In step b, a mechanical pump is used to draw the vacuum to below 10 Pa, and then a molecular pump is used to draw the vacuum to 1×10 -3 Pa, turn off the molecular pump, fill with argon to 0.02 MPa and seal.
4. The method for preparing a room temperature magnetostrictive composite material according to claim 1, characterized in that: In step d, the CoMnSi particles are dried using an oven or a hair dryer.
5. The method for preparing a room temperature magnetostrictive composite material according to claim 1, characterized in that: In step e, a mechanical pump is used to draw the vacuum to below 10 Pa, and then a molecular pump is used to draw the vacuum to 1×10 -3 Pa sealed.
6. The method for preparing a room temperature magnetostrictive composite material according to claim 1, characterized in that: In step g, the volume ratio of CoMnSi to epoxy resin is higher than 1:1.